Mastering language use and usage: repositions perceived according to cognitive linguistics - Fernando, Sérgio Manuel Coelho; Dias, Alfrancio Ferreira (Série-Estudos, 2017)
Mastering prepositions has often been difficult for English language learners as a consequence of their polysemous nature and the sheer number of them in the English language. Most of the evaluations of the scientific output of the English language learners have established that prepositional addition, omission, and substitution account for most of the syntactic errors. For this reason, it is important for tutors to come up with effective instructional methods, since prepositions present such an immense challenge for the English language learners. Teaching prepositions are difficult due to various reasons. The present article has as objective the approach on the application of Prepositions and how structure and meaning may be perceived according to cognitive linguistics, based on other articles / books that served as bibliographical research for the construction of some ideas.